2015
DOI: 10.31729/jnma.2773
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Tuberculosis with Paraplegia in Pregnancy: a Case Report with Management of Spinal TB in Pregnancy

Abstract: Spinal tuberculosis leading to paraplegia is uncommon in pregnancy and is a diagnostic and therapeutic challenge. We report a case of tubercular paraplegia presenting at 35 weeks of gestation. She was managed with Anti-tubercular drugs and did not require surgical intervention. Her neurological status improved and she was allowed to go in labour. She delivered a healthy term infant by cesarean. At three months follow-up, both mother and child are doing well.  Keywords: paraplegia; pregnancy; spinal tuber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“… 19 24 28 29 39 44 45 47 49 50 52 54 55 57–59 61 64 66 68 72–76 Some resulted in recommendation and subsequent termination of pregnancy, 56 57 59 77 78 induced abortion 49 62 79 or unplanned caesarean section or induction. 24 25 27 29 36 38 39 53 72 74 For example, one case report described a woman with suspected genitourinary TB prior to pregnancy who suffered from severe pre-eclampsia and postpartum complication of pyelonephritis with unplanned induction. 72 …”
Section: Resultsmentioning
confidence: 99%
“… 19 24 28 29 39 44 45 47 49 50 52 54 55 57–59 61 64 66 68 72–76 Some resulted in recommendation and subsequent termination of pregnancy, 56 57 59 77 78 induced abortion 49 62 79 or unplanned caesarean section or induction. 24 25 27 29 36 38 39 53 72 74 For example, one case report described a woman with suspected genitourinary TB prior to pregnancy who suffered from severe pre-eclampsia and postpartum complication of pyelonephritis with unplanned induction. 72 …”
Section: Resultsmentioning
confidence: 99%
“…Mohanty et al found an aggressive hemangioma causing paraparesis in term pregnant lady presenting for CS. She recovered eventually without surgery [ 1 , 2 , 3 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-traumatic paraplegia developing in pregnancy is rare phenomenon with only sporadic reports [ 1 , 2 , 3 ]. Spontaneous development of spinal epidural hematoma (SEH) without any predisposing factor is rare and even more sporadic in pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…2 To our knowledge, only three case reports of acute-onset paraplegia in term pregnancy have been noted in the past two decades. 3,4,5…”
Section: Discussionmentioning
confidence: 99%